The Influence of Subjective Factors on the Development of the Transformational Style of Leadership - Bilal El TOUFAILI (Revista de Management Comparat International)
Managers have to face the complexity of the technological and informational environment, social change, increasing entrepreneurial activity, accelerating technological developments and a more educated and skilled workforce. Leadership is a critical element in the success of an organization. Dynamic and efficient leadership involves creating a vision and action plan to ensure that organizations are client-centered, as well as creating a favourable environment for employees to optimize productivity and innovation. Although the elements that can influence leadership are multiple, and with regard to the transformational leadership style is an interpretable measure of how it takes place, we consider it appropriate to analyse and measure the factors that contribute to its formation. The opportunity of undertaking this research derives from the need to identify the antecedents that contribute to the formation of the transformational leadership style.